Work-Life balance of employees among business process outsourcing companies in Ilocos Norte, Philippines - Aquino, Charmaine A. (Ilocos Norte : [s.n.], 2019)
This study determined the work-life balance of Business Process Outsourcing employees in Ilocos Norte, Philippines. The descriptive correlational research design was used using a survey questionnaire to gather data. Involved as respondents of the study were 100 BPO employees who are working at the three BPO Companies in Ilocos Norte.
Bibliography: pages 69-75.
CHED-La Union
Keywords: Employees -- Attitude; Employee motivation